OVERVIEW OF GLOMERULAR HYPERTROPHY AND HYDROPIC DEGENERATION OF DIABETIC RAT KIDNEY MODELS IN GIVING TOMAN FISH - Carabelly, Amy Nindia; Sinaga, Udur; Dewi, Nurdiana (E-Prodenta Journal of Dentistry, 2021)
Background: Traditional medicine is increasingly favored by the community as an effort to maintain and treat health because it has low side effects and is easy to obtain. Low side effects in administering traditional medicines if the dosage is right, so it is necessary to do an acute toxicity test. One of the consumers of traditional medicine is diabetes mellitus (DM) sufferer. DM can cause delay wound healing. Toman fish is proven to accelerate wound healing. DM sufferers need special attention to their kidneys because in addition to the toxic effects caused by improper doses of traditional medicine, the kidneys can also experience diabetic nephropathy. Objectives: To analyze changes in glomerular hypertrophy and hydropic degeneration in the administration of 16 mL / KgBW Toman fish extract orally for 14 days in diabetic wistar rat kidneys. Methods: This study was a true experimental design with a post test only with control group design. The study was divided into a treatment group of toman fish extract at a dose of 16 mL / Kg BW orally for 14 days in diabetic rat kidney models and a control group in the form of feeding only. Results: The administration of toman fish extract in DM rat showed changes in the glomerular hypertrophy picture of 25-50% and decreased glomerular hypertrophy score which was significantly different from the control group. There was no feature of hydropic degeneration in either group. Conclusions: Giving toman fish extract to DM rat can reduce glomerular hypertrophy and does not cause hydropic degeneration